Toleransi Antarumat Beragama dalam Meningkatkan Persatuan Dan Kesatuan Bangsa di Desa Pasir Jaya - Ryan Prayogi; Rina Ari Rohmah (Universitas Negeri Medan, 2020)
The writing of this article aims to find out the basic values that form the basis of tolerance and tolerance forms among Muslims, Buddhists and Christians in Pasir Jaya Village, Rambah Hilir District, Rokan Hulu Regency. The Research Participants are the Village Head, Community Leaders, and Prominent Islamic, Christian and Buddhist leaders, Youth Chairperson, PKK Chairperson and Pasir Jaya Village Community. This research site was conducted in Pasir Jaya Village, Rambah Hilir District, Rokan Hulu Regency, Riau Province. Data collection techniques using observation, interviews, documentation and analyzed qualitatively through data analysis techniques using data reduction, data display and data verification. This study concludes that the basic values on which tolerance is formed between Muslims, Christians and Buddhists are normatively found in religious values and cultural values. Meanwhile, empirically include: human values related to help, nationalism values related to cooperation and mutual cooperation, historical values related to respect, and democratic values related to deliberation. While the form of tolerance is manifested in social interaction and cooperation which includes: (1) Cooperation in development, (2) Participation in weddings, (3) participating in events of death, (4) Attitudes of respect and respect for religious celebrations, and (5) ) Deliberation in village activities.